Cobalt-doped nickel-zinc ferrite material and preparation method and application thereof

By doping cobalt in nickel-zinc ferrite, the existing spinel ferrite materials have large thickness, narrow frequency band and low absorption strength, and the thickness of the absorbing material has been achieved, which has improved the absorption capacity of the high-frequency region.

CN119637948APending Publication Date: 2025-03-18GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411812323.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing spinel ferrite materials have problems such as thick thickness, narrow absorption bandwidth and low absorption strength.

Method used

By doping cobalt into nickel-zinc ferrite, the electromagnetic performance of the material is regulated, magnetic loss and impedance matching are enhanced, thereby improving the absorption peak position and improving the material's absorption capacity in high-frequency regions.

Benefits of technology

The thickness of the absorbing material is "thin", the frequency band is "wide" and "strong" absorption, which significantly enhances the absorption capacity of nickel-zinc ferrite materials in the X-band and Ku bands.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637948A_ABST
    Figure CN119637948A_ABST
Patent Text Reader

Abstract

The invention provides a cobalt-doped nickel-zinc ferrite material and a preparation method and application thereof, the chemical general formula of the cobalt-doped nickel-zinc ferrite material is Ni < 0.5-x > Zn < 0.5-y > Co < x + y > Fe2O4, 0 < = x < = 0.4, 0 < = y < = 0.4, and 0 < x + y < = 0.4. According to the cobalt-doped nickel-zinc ferrite material disclosed by the invention, by doping cobalt, the material can better absorb incident electromagnetic waves, and the position of an absorption peak is changed, so that the wave-absorbing capacity of the nickel-zinc ferrite material in a high-frequency region is improved, and the wave-absorbing material is thin in thickness, wide in frequency band and high in absorption capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electromagnetic wave absorbing materials and relates to a cobalt-doped nickel-zinc ferrite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of modern electronics and communication technology, electromagnetic waves of various frequency bands are generated in life. Electromagnetic radiation not only interferes with communication systems, but also affects the environment and human health. It is necessary to develop nanomaterials with excellent performance for electromagnetic wave absorption. NiZn ferrite, as a soft magnetic material with spinel structure, has the characteristics of high saturation magnetization, high resistivity and high Curie temperature. It shows its importance in many application fields. Among them, spinel is widely used in electromagnetic wave absorption materials due to its strong magnetic loss, low cost and easy synthesis.

[0003] Ion doping is an important way to improve the microwave absorption performance of spinel. 0.7 Zn 0.3 A 0.05 Fe 1.95 O4 (A = La, Ce, Nd) powder, and by doping different elements (La, Ce, Nd), better impedance matching is formed to enhance the microwave absorption effect. It is observed that at 13.8GHz, the minimum reflection loss is -17.5dB. In the prior art, Co, Cu, Zn doped spinel ferrite Ni 0.5 X 0.3 Ce 0.2 Fe2O4 (X = Co, Cu, Zn), it was observed that the minimum reflection loss of the Zn-doped sample was -51.5 dB at 17.6 GHz with a thickness of 2.8 mm. In the prior art, Mn-doped spinel ferrite (CoNiCuZn) was also prepared by solution combustion method. 1-x Mn x Fe2O4, by controlling the element level of Mn doping (x = 0.05, 0.1, 0.2 and 0.3), obtained satisfactory reflection loss in the sample with x = 0.3. However, the current spinel ferrite still has the disadvantages of thick thickness, narrow absorption bandwidth and absorption intensity to be improved.

[0004] Therefore, there is an urgent need to develop a new spinel ferrite absorbing material that can solve the problems of thick ferrite, narrow absorption bandwidth and low absorption intensity. Summary of the invention

[0005] The object of the present invention is to provide a cobalt-doped nickel-zinc ferrite material and a preparation method and application thereof. The cobalt-doped nickel-zinc ferrite material is doped with cobalt to make the material better absorb incident electromagnetic waves and change the absorption peak position, thereby improving the absorbing ability of the nickel-zinc ferrite material in the high-frequency region, and achieving the "thin" thickness, "wide" frequency band and "strong" absorption of the absorbing material.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a cobalt-doped nickel-zinc ferrite material, wherein the chemical formula of the cobalt-doped nickel-zinc ferrite material is Ni 0.5-x Zn 0.5-y Co x+y Fe2O4, wherein 0≤x≤0.4, 0≤y≤0.4, and 0<x+y≤0.4.

[0008] The present invention dopes cobalt into nickel-zinc ferrite, regulates the electromagnetic properties of nickel-zinc ferrite, enhances the magnetic loss of nickel-zinc ferrite, improves impedance matching, and enables the nickel-zinc ferrite material to better absorb incident electromagnetic waves. In addition, the present invention can change the absorption peak position by adjusting the cobalt doping concentration, thereby significantly enhancing the wave absorbing ability of the nickel-zinc ferrite material in the high-frequency region.

[0009] The 0≤x≤0.4 may be, for example, 0, 0.1, 0.2, 0.3 or 0.4, 0≤y≤0.4 may be, for example, 0, 0.1, 0.2, 0.3 or 0.4, and x and y are not 0 at the same time, and the 0<x+y≤0.4 may be, for example, 0.1, 0.2, 0.3 or 0.4, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0010] Preferably, 0.1≤x+y≤0.3, for example, it can be 0.1, 0.2, 0.25, 0.27 or 0.3, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0011] The value of x+y in the present invention can reflect the doping amount of cobalt, preferably within a specific range, and can further improve the nickel-zinc ferrite material. If the value of x+y is too small and the doping amount of cobalt is small, the matching thickness is larger. If the value of x+y is too large and the doping amount of cobalt is too much, the absorption peak moves to a higher frequency greater than 18 GHz.

[0012] Preferably, x=0, 0.1≤y≤0.3, for example, it can be 0.1, 0.2, or 0.3, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0013] In the present invention, when cobalt is doped, the amount of nickel and / or zinc is appropriately reduced. Therefore, when x and y are within a specific preferred range, the wave absorbing effect can be significantly enhanced.

[0014] The cobalt-doped nickel-zinc ferrite material absorbs in both the X-band and the Ku-band, the X-band is in the range of 8-12 GHz, for example, 8 GHz, 10 GHz or 12 GHz, and the Ku-band is in the range of 12-18 GHz, for example, 12 GHz, 14 GHz, 16 GHz or 18 GHz, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] The cobalt-doped nickel-zinc ferrite absorbing material of the present invention has a strong absorption capacity in the X-band and the Ku-band, that is, the cobalt-doped nickel-zinc ferrite material of the present invention has a high absorption capacity in the high-frequency region.

[0016] Preferably, the operating temperature of the cobalt-doped nickel-zinc ferrite material is -40 to 400°C, for example, it can be -40°C, 0°C, 60°C, 100°C, 160°C, 200°C, 250°C, 300°C or 400°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] In a second aspect, the present invention provides a method for preparing the cobalt-doped nickel-zinc ferrite material as described in the first aspect, the preparation method comprising the following steps:

[0018] (1) mixing a nickel source, an iron source, a zinc source, a cobalt source, a complexing agent and a solvent according to a formula to obtain a mixed solution;

[0019] (2) mixing a pH adjuster with the mixed solution of step (1), adjusting the pH, and then stirring at a constant temperature to obtain a gel;

[0020] (3) The gel of step (2) is dried, heat treated and calcined in sequence to obtain the cobalt-doped nickel-zinc ferrite material.

[0021] Compared with the method of solid-phase mixing and calcining of oxides, the preparation method of the present invention can uniformly and quantitatively incorporate elements, achieve uniform doping at the molecular level, and is conducive to the preparation of high-performance absorbing materials.

[0022] Preferably, the molar ratio of the nickel source, zinc source, cobalt source and iron source in step (1) is (0.1-0.5):(0.1-0.5):(0-0.4):2, but does not include (0.1-0.5):(0.1-0.5):0:2, for example, it can be 0.4:0.5:0.1:2, 0.5:0.4:0.1:2, 0.3:0.5:0.2:2 or 0.3:0.3:0.4:2, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] Preferably, the nickel source, iron source, zinc source and cobalt source independently include any one of nitrate, acetate or chloride, or a combination of at least two of them, and the purity of the raw materials is analytical grade or higher.

[0024] Preferably, the complexing agent in step (1) comprises citric acid.

[0025] Preferably, the ratio of the molar amount of the complexing agent in step (1) to the total molar amount of the nickel source, iron source, zinc source and cobalt source is (1-5):1, for example, it can be 1:1, 2.5:1, 3:1, 4.5:1 or 5:1, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable, preferably (1-3):1.

[0026] Preferably, the step (1) of mixing the nickel source, iron source, zinc source, cobalt source, complexing agent and solvent comprises first stirring and mixing the nickel source, iron source, zinc source, cobalt source and solvent, and then adding complexing agent solution for mixing.

[0027] Preferably, the pH adjuster in step (2) comprises aqueous ammonia.

[0028] Preferably, the concentration of the aqueous ammonia is 25-50wt%, for example, 25wt%, 30wt%, 35wt%, 45wt% or 50wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] Preferably, the pH value in step (2) is adjusted to 5-8.5, for example, 5, 6.5, 7.5, 8 or 8.5, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0030] Preferably, the temperature of the constant temperature stirring in step (2) is 75-95°C, for example, 75°C, 80°C, 85°C, 90°C or 95°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0031] Preferably, the constant temperature stirring can be performed in a water bath or an oil bath.

[0032] Preferably, the drying temperature in step (3) is 95-125°C, for example, 95°C, 100°C, 105°C, 110°C, 115°C or 125°C, and the drying time is 10-48h, for example, 10h, 16h, 20h, 24h, 30h, 36h or 48h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0033] Preferably, the temperature of the heat treatment in step (3) is 100-350°C, for example, 100°C, 140°C, 180°C, 220°C, 260°C, 300°C or 350°C, and the time is 0.1-3h, for example, 0.1h, 0.8h, 1.4h, 2.2h or 3h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0034] Preferably, the heating rate of the calcination in step (3) is 2-10°C / min, for example, 2°C / min, 5°C / min, 7.5°C / min or 10°C / min, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable, preferably 2-5°C / min.

[0035] By controlling the heating rate of calcination within a certain range, the present invention can increase the crystal growth time, form larger grains, increase the dielectric loss of the material, and achieve better wave absorbing effect.

[0036] Preferably, the calcination temperature in step (3) is 900-1300°C, for example, 900°C, 1100°C, 1200°C, 1250°C or 1300°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable, preferably 1100-1300°C.

[0037] Preferably, the calcination time in step (3) is 3-21 h, for example, 3 h, 6 h, 10 h, 18 h or 21 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0038] In the present invention, the heating method for roasting includes microwave heating and / or electric heating.

[0039] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:

[0040] (1) mixing a nickel source, an iron source, a zinc source, a cobalt source, a complexing agent and a solvent to obtain a mixed solution;

[0041] The molar ratio of the nickel source, zinc source, cobalt source and iron source is (0.1-0.5):(0.1-0.5):(0-0.4):2, but excluding (0.1-0.5):(0.1-0.5):0:2; the molar ratio of the complexing agent to the total molar ratio of the nickel source, iron source, zinc source and cobalt source is (1-5):1;

[0042] (2) mixing a pH adjuster with the mixed solution of step (1), adjusting the pH to 5-8.5, and then stirring at a constant temperature of 75-95° C. to obtain a gel;

[0043] (3) Drying the gel of step (2) at 95-125° C. for 10-48 h, then heat treating at 100-350° C. for 0.1-3 h, and finally heating to 900-1300° C. at a heating rate of 2-10° C. / min and calcining for 3-21 h to obtain the cobalt-doped nickel-zinc ferrite material.

[0044] In a third aspect, the present invention provides an application of the cobalt-doped nickel-zinc ferrite material as described in the first aspect, wherein the application includes use in the field of wave absorption.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] (1) The present invention dopes cobalt into nickel-zinc ferrite and controls the molar ratio of nickel, zinc and cobalt. The nickel-zinc ferrite has strong absorption in the X-band and Ku-band, and can reduce the matching thickness, broaden the absorption frequency band, significantly improve the dielectric properties of the material and enhance the microwave absorption performance.

[0047] (2) The preparation method of the present invention has low production cost and simple process. The prepared cobalt-doped nickel-zinc ferrite absorbing material has the advantages of adjustable absorbing frequency band, large absorbing intensity and high operating temperature.

[0048] (3) The nickel-zinc ferrite material of the present invention maintains relatively stable wave absorbing performance within a larger cobalt doping range, which makes it possible to be used as a base material for other composite materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 X-ray diffraction patterns of the cobalt-doped nickel-zinc ferrite material described in Example 1 and the nickel-zinc ferrite material described in Comparative Example 1;

[0050] Figure 2 This is a diagram showing the wave absorption effect of the cobalt-doped nickel-zinc ferrite material described in Example 1;

[0051] Figure 3 This is a diagram showing the wave absorption effect of the cobalt-doped nickel-zinc ferrite material described in Example 2;

[0052] Figure 4This is a diagram showing the wave absorption effect of the cobalt-doped nickel-zinc ferrite material described in Example 3;

[0053] Figure 5 This is a diagram showing the wave absorption effect of the cobalt-doped nickel-zinc ferrite material described in Example 4;

[0054] Figure 6 This is a diagram showing the wave absorption effect of the cobalt-doped nickel-zinc ferrite material described in Example 5;

[0055] Figure 7 This is a diagram showing the wave absorption effect of the cobalt-doped nickel-zinc ferrite material described in Example 6;

[0056] Figure 8 This is a diagram showing the wave absorption effect of the cobalt-doped nickel-zinc ferrite material described in Example 7;

[0057] Fig. 9 This is a diagram showing the wave absorption effect of the nickel-zinc ferrite material described in Comparative Example 1. DETAILED DESCRIPTION

[0058] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0059] Example 1

[0060] This embodiment provides a cobalt-doped nickel-zinc ferrite material, the chemical formula of which is Ni 0.5 Zn 0.2 Co 0.3 Fe2O4, the preparation method of the cobalt-doped nickel-zinc ferrite material comprises the following steps:

[0061] (1) nickel nitrate hexahydrate, zinc nitrate hexahydrate, cobalt nitrate hexahydrate, ferric nitrate nonahydrate and deionized water were stirred and mixed in a molar ratio of 0.5:0.2:0.3:2.0, and then a monohydrate citric acid aqueous solution was added thereto, and the mixture was stirred for 3 hours to obtain a mixed solution;

[0062] The molar ratio of the monohydrated citric acid to the total molar ratio of the iron source, the nickel source, the zinc source, and the cobalt source is 1:1;

[0063] (2) adding 25% ammonia water to the mixed solution of step (1) until the pH value of the mixed solution reaches 7.0, and then placing the mixed solution in an oil bath thermostat and stirring at 95° C. for 8 h to obtain a viscous gel;

[0064] (3) drying the viscous gel in step (2) at 100° C. for 24 h in a forced air drying oven, heat treating at 300° C. for 0.3 h, grinding, heating to 1250° C. at a heating rate of 5° C. / min, calcining and keeping the temperature for 4 h to obtain the cobalt-doped nickel-zinc ferrite material.

[0065] The X-ray diffraction pattern of the cobalt-doped nickel-zinc ferrite material prepared in this embodiment is as follows: Figure 1 As shown, Figure 1 The curve (b) in FIG. 1 is the cobalt-doped nickel-zinc ferrite material described in this embodiment, Figure 1 It can be seen that the sample after doping with cobalt is a pure spinel phase. Figure 2 This is a diagram showing the wave absorption effect of the cobalt-doped nickel-zinc ferrite material prepared in this embodiment. It has strong absorption in the high frequency band, with a minimum reflection loss of -73.53 dB, a small matching thickness of 2.04 mm, and an effective absorption bandwidth of 8.21 GHz.

[0066] Example 2

[0067] This embodiment provides a cobalt-doped nickel-zinc ferrite material, the chemical formula of which is Ni 0.5 Zn 0.3 Co 0.2 Fe2O4, the preparation method of the cobalt-doped nickel-zinc ferrite material comprises the following steps:

[0068] (1) nickel nitrate hexahydrate, zinc nitrate hexahydrate, cobalt nitrate hexahydrate, ferric nitrate nonahydrate and deionized water were stirred and mixed in a molar ratio of 0.5:0.3:0.2:2.0, and then a monohydrate citric acid aqueous solution was added thereto, and the mixture was stirred for 3 hours to obtain a mixed solution;

[0069] The molar ratio of the monohydrated citric acid to the total molar ratio of the iron source, the nickel source, the zinc source, and the cobalt source is 1:1;

[0070] (2) adding 25% ammonia water to the mixed solution of step (1) until the pH value of the mixed solution reaches 7.0, and then placing the mixed solution in an oil bath thermostat and stirring at 95° C. for 8 h to obtain a viscous gel;

[0071] (3) drying the viscous gel in step (2) at 100° C. for 24 h in a forced air drying oven, heat treating at 300° C. for 0.3 h, grinding, heating to 1250° C. at a heating rate of 5° C. / min, calcining and keeping the temperature for 4 h to obtain the cobalt-doped nickel-zinc ferrite material.

[0072] The wave absorption effect of the cobalt-doped nickel-zinc ferrite material prepared in this embodiment is shown in the figure below: Figure 3As shown, it has strong absorption in the low frequency band, with a minimum reflection loss of -44.67dB. In the high frequency band, the matching thickness is small, reaching 2.58mm, with a minimum reflection loss of -67.04dB, and an effective absorption bandwidth of 8.14GHz.

[0073] Example 3

[0074] This embodiment provides a cobalt-doped nickel-zinc ferrite material, the chemical formula of which is Ni 0.5 Zn 0.2 Co 0.3 Fe2O4, the preparation method of the cobalt-doped nickel-zinc ferrite material comprises the following steps:

[0075] (1) nickel nitrate hexahydrate, zinc nitrate hexahydrate, cobalt nitrate hexahydrate, ferric nitrate nonahydrate and deionized water were stirred and mixed in a molar ratio of 0.5:0.2:0.3:2.0, and then a monohydrate citric acid aqueous solution was added thereto, and the mixture was stirred for 3 hours to obtain a mixed solution;

[0076] The molar ratio of the monohydrated citric acid to the total molar ratio of the iron source, the nickel source, the zinc source, and the cobalt source is 5:1;

[0077] (2) adding 25% ammonia water to the mixed solution of step (1) until the pH value of the mixed solution reaches 8.5, and then placing the mixed solution in an oil bath thermostat and stirring at 125° C. for 48 hours to obtain a viscous gel;

[0078] (3) drying the viscous gel in step (2) at 125° C. for 20 h in a forced air drying oven, heat treating at 100° C. for 2 h, grinding, heating to 900° C. at a heating rate of 2° C. / min, calcining, and keeping the temperature for 3 h to obtain the cobalt-doped nickel-zinc ferrite material.

[0079] The wave absorption effect of the cobalt-doped nickel-zinc ferrite material described in this embodiment is shown in the figure below. Figure 4 shown.

[0080] Example 4

[0081] This embodiment provides a cobalt-doped nickel-zinc ferrite material. The cobalt-doped nickel-zinc ferrite material is the same as that of Embodiment 1 except that the calcination holding time in step (3) of the preparation method is 21 hours.

[0082] The wave absorption effect of the cobalt-doped nickel-zinc ferrite material described in this embodiment is shown in the figure below. Figure 5 shown.

[0083] Example 5

[0084] This embodiment provides a cobalt-doped nickel-zinc ferrite material, the chemical formula of which is Ni 0.5Zn 0.4 Co 0.1 Except for Fe2O4, the rest is the same as Example 1.

[0085] The preparation method of the cobalt-doped nickel-zinc ferrite material described in this embodiment is the same as that of Example 1 except that the preparation method is adaptively changed according to the formula amount.

[0086] The wave absorption effect of the cobalt-doped nickel-zinc ferrite material described in this embodiment is shown in the figure below. Figure 6 shown.

[0087] Example 6

[0088] This embodiment provides a cobalt-doped nickel-zinc ferrite material, the chemical formula of which is Ni 0.5 Zn 0.1 Co 0.4 Except for Fe2O4, the rest is the same as Example 1.

[0089] The preparation method of the cobalt-doped nickel-zinc ferrite material described in this embodiment is the same as that of Example 1 except that the preparation method is adaptively changed according to the formula amount.

[0090] The wave absorption effect of the cobalt-doped nickel-zinc ferrite material described in this embodiment is shown in the figure below. Figure 7 shown.

[0091] Example 7

[0092] This embodiment provides a cobalt-doped nickel-zinc ferrite material, the chemical formula of which is Ni 0.2 Zn 0.5 Co 0.3 Except for Fe2O4, the rest is the same as Example 1.

[0093] The preparation method of the cobalt-doped nickel-zinc ferrite material described in this embodiment is the same as that of Example 1 except that the preparation method is adaptively changed according to the formula amount.

[0094] The wave absorption effect of the cobalt-doped nickel-zinc ferrite material described in this embodiment is shown in the figure below. Figure 8 shown.

[0095] Comparative Example 1

[0096] This comparative example provides a nickel-zinc ferrite material, the chemical formula of which is Ni 0.5 Zn 0.5 Except for Fe2O4, the rest is the same as Example 1.

[0097] The preparation method of the nickel-zinc ferrite material described in this embodiment is the same as that of Example 1 except that the preparation method is adaptively changed according to the formula amount.

[0098] The XRD pattern of the nickel-zinc ferrite material in this comparative example is as follows Figure 1 As shown, Figure 1 (a) curve in the figure; the wave absorption effect diagram of the nickel-zinc ferrite material described in this comparative example is as shown in Fig. 9 As shown by Fig. 9 It can be seen that the material has poor microwave absorption performance when it is not doped with cobalt.

[0099] The materials of the above-mentioned embodiments and comparative examples were subjected to performance tests. The specific test method was as follows: after the samples were mixed with 15wt% paraffin, they were pressed into a ring-shaped device. The inner diameter / outer diameter of the device was 3 / 7mm and the thickness was about 2mm. Then, a vector network analyzer (VNA, Agilent N5222A) was used to measure the dynamic electromagnetic parameters using the transmission-reflection coaxial line method in the frequency range of 2-18GHz. The reflection loss (RL) of a certain thickness was calculated according to the transmission line theory. The test results are shown in Table 1:

[0100] Table 1

[0101]

[0102] From Table 1 we can see that:

[0103] (1) It can be seen from Examples 1 to 2 and Comparative Example 1 that changing the cobalt doping ratio can effectively adjust its absorption band, while reducing the matching thickness to achieve strong absorption in the X band and Ku band.

[0104] (2) It can be seen from Example 1 and Comparative Example 1 that when the cobalt element is not doped, the wave absorption performance of the material is poor, the matching thickness is large, and the effective absorption bandwidth is narrow.

[0105] (3) It can be seen from Example 1 and Examples 3 to 4 that changing the sintering conditions can adjust the absorbing performance, and increasing the sintering and heat preservation time can further enhance the absorbing performance.

[0106] (4) The cobalt-doped nickel-zinc ferrite materials described in Examples 1 to 5 of the present invention have higher magnetic loss and good impedance matching, strong absorption in the X-band and Ku-band, and an effective absorption bandwidth of 8.21 GHz.

[0107] (5) It can be seen from Example 1 and Example 6 that when x+y is larger, that is, when the cobalt doping amount is larger, the absorbing performance will decrease.

[0108] (6) It can be seen from Examples 1 and 7 that in the present invention, when x+y is within a specific range, that is, when the cobalt doping amount is at a specific cobalt content, x and y can take different values, and preferably x and y are also within a specific range, which can further improve the absorbing performance of the material.

[0109] (7) It can be seen from Examples 1-7 that in the present invention, x+y is preferably 0.1-0.3, which can further ensure the wave absorbing performance of the material.

[0110] In summary, the present invention provides a cobalt-doped nickel-zinc ferrite material and a preparation method and application thereof. The cobalt-doped nickel-zinc ferrite material is doped with cobalt to make the material better absorb the incident electromagnetic wave and change the absorption peak position, thereby improving the absorbing ability of the nickel-zinc ferrite material in the high-frequency region, and achieving the "thin" thickness, "wide" frequency band and "strong" absorption of the absorbing material.

[0111] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A cobalt-doped nickel-zinc ferrite material, characterized in that: The chemical formula of the cobalt-doped nickel-zinc ferrite material is Ni 0.5-x Zn 0.5-y Co x+y Fe2O4, wherein 0≤x≤0.4, 0≤y≤0.4, and 0<x+y≤0.

4.

2. The cobalt-doped nickel-zinc ferrite material according to claim 1, characterized in that: 0.1≤x+y≤0.3; Preferably, x=0, 0.1≤y≤0.

3.

3. The cobalt-doped nickel-zinc ferrite material according to claim 1 or 2, characterized in that: The cobalt-doped nickel-zinc ferrite material absorbs simultaneously in the X-band and the Ku-band, the X-band is in the range of 8-12 GHz, and the Ku-band is in the range of 12-18 GHz; Preferably, the operating temperature of the cobalt-doped nickel-zinc ferrite material is -40 to 400°C.

4. A method for preparing the cobalt-doped nickel-zinc ferrite material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing a nickel source, an iron source, a zinc source, a cobalt source, a complexing agent and a solvent according to a formula to obtain a mixed solution; (2) mixing a pH adjuster with the mixed solution of step (1), adjusting the pH, and then stirring at a constant temperature to obtain a gel; (3) The gel of step (2) is dried, heat treated and calcined in sequence to obtain the cobalt-doped nickel-zinc ferrite material.

5. The preparation method according to claim 4, characterized in that: The complexing agent in step (1) comprises citric acid; Preferably, the ratio of the molar amount of the complexing agent in step (1) to the total molar amount of the nickel source, the iron source, the zinc source and the cobalt source is (1-5):1, preferably (1-3):1; Preferably, the step (1) of mixing the nickel source, iron source, zinc source, cobalt source, complexing agent and solvent comprises first stirring and mixing the nickel source, iron source, zinc source, cobalt source and solvent, and then adding complexing agent solution for mixing.

6. The preparation method according to claim 4 or 5, characterized in that: The pH adjusting agent in step (2) comprises aqueous ammonia; Preferably, the concentration of the aqueous ammonia is 25-50 wt %.

7. The preparation method according to any one of claims 4 to 6, characterized in that: Step (2) wherein the pH is adjusted to 5-8.5; Preferably, the temperature of the constant temperature stirring in step (2) is 75-95°C.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The drying temperature in step (3) is 95-125° C. and the drying time is 10-48 h; Preferably, the heat treatment temperature in step (3) is 100-350° C. and the time is 0.1-3 h; Preferably, the heating rate of the calcination in step (3) is 2-10°C / min, preferably 2-5°C / min; Preferably, the calcination temperature in step (3) is 900-1300° C. and the calcination time is 3-21 hours.

9. The preparation method according to any one of claims 4 to 8, characterized in that: The preparation method comprises the following steps: (1) mixing a nickel source, an iron source, a zinc source, a cobalt source, a complexing agent and a solvent to obtain a mixed solution; The molar ratio of the nickel source, zinc source, cobalt source and iron source is (0.1-0.5):(0.1-0.5):(0-0.4):2, but excluding (0.1-0.5):(0.1-0.5):0:2; the molar ratio of the complexing agent to the total molar ratio of the nickel source, iron source, zinc source and cobalt source is (1-5):1; (2) mixing a pH adjuster with the mixed solution of step (1), adjusting the pH to 5-8.5, and then stirring at a constant temperature of 75-95° C. to obtain a gel; (3) Drying the gel of step (2) at 95-125° C. for 10-48 h, then heat treating at 100-350° C. for 0.1-3 h, and finally heating to 900-1300° C. at a heating rate of 2-10° C. / min and calcining for 3-21 h to obtain the cobalt-doped nickel-zinc ferrite material.

10. An application of the cobalt-doped nickel-zinc ferrite material according to any one of claims 1 to 3, characterized in that: The application includes use in the field of wave absorption.